Private sector savings - Renáta Pitonáková (DANUBE: Law, Economics and Social Issues Review, 2018)
The majority of household savings are in the form of bank deposits. It is therefore of interest for credit institutions to tailor their deposit policy for getting finances from non-banking entities and to provide the private sector with the loans that are necessary for investment activities and consumption. This paper deals with the determinants of the saving rate of the private sector of Slovakia. Economic, financial and demographic variables influence savings. Growth of income per capita, private disposable income, elderly dependency ratio, real interest rate and inflation have a positive impact on savings, while increases in public savings indicate a crowding out effect. The inflation rate implies precautionary savings, and dependency ratio savings for bequest. There are also implications for governing institutions deciding on the implementation of appropriate fiscal and monetary operations.
Keywords: 330; Private Sector; Saving Rate; Precautionary Savings; Public Savings